SENSORY EVALUATION OF NOODLES MADE FROM WALUH (Cucurbita Moschata) FLOUR AND SNAKEHEAD FISH (Channa striata) AS ALTERNATIF FOOD OF HIGH FIBER, VITAMIN A AND PROTEIN - Adhyanti Adhyanti; Wery Aslinda; Marlinda Kartika Apandano (Universitas Tanjungpura, 2020)
Food diversification efforts to reduce dependence on wheat flour by exploring other food potentials such as pumpkin pumpkin (Curcurbita Moschata) and snakehead fish (Channa Striata) which have long been known to the Indonesian public need to be done. The aim of this study was to determine the acceptability of noodles made frompumpkin flour and snakehead fish. Type of research is an organoleptic test (hedonic quality) on noodle products with 4 parameters, namely color, aroma, texture and taste. 1: 1: 1), product 2 (0: 1: 1), and product 3 (0.66: 1: 1). The panelists in this study were 25 somewhat trained researchers. The results show that the level of liking (acceptance) for product 1, product 2 and product 3 for color parameters respectively were 68%, 60%, 52%; aroma 40%, 52%, 44%; texture 36%, 48%, 48%; and taste 36%, 52%, 40%. The Kruskal wallis test showed no difference in color, aroma, texture, and taste for the all products. The conclusion is that the color parameters of product 1, product 2, and product 3 are accepted, while the aroma parameter received is product 2, and no texture parameter is accepted, and the taste parameter received is only product 2. It is recommended that further modification of the composition of the ingredients be made so that the texture of the noodles can be more acceptable.